Kasih Ibu Sepanjang Masa: Optimisme Ibu dalam Menghadapi Anak yang Kecanduan Game Online - Yonathan Setyawan; Andreas Happy Fathur; Nadia Pramudita (Fakultas Psikologi Universitas Kristen Satya Wacana, 2024)
The purpose of this study is to determine the definition of maternal optimism in dealing with children who are addicted to online games. The subject in the study amounted to one person selected based on the criteria, namely mothers with children who have an online game addiction. This data collection technique uses semi-structured interviews with the Theory-Led Thematic Analysis approach. The results concluded that the subject has optimism in children who experience online game addiction based on aspects of optimism, namely the permanence aspect, which can be seen from the subject overcoming the problem of children's addiction by limiting the hours of playing the game and supervising the child's behavior in playing online games. Then the pervasiveness aspect is that the subject knows the specific cause of the child's behavior or emotions and knows why close relatives talk about the child's negative behavior or emotions from the impact of online gaming. In the personalization aspect, where the subject is involved in supervising the child, the subject has succeeded in dealing with the problem by removing games that trigger the child's negative emotions and guiding the child to convey his emotions properly.